How perceived changes in the ethical culture of organizations influence the well-being of managers: a two-year longitudinal study. Issue 3 (3rd May 2016) - Huhtala, Mari; Kaptein, Muel; Feldt, Taru
Abstract : The first aim of this study was to identify long-term patterns of ethical organizational culture based on the perceptions of 368 Finnish managers over a period of two years. The second aim was to investigate whether there is a difference in the long-term occupational well-being (burnout and work engagement) of managers exhibiting different patterns of ethical culture. Based on latent profile analysis, five different patterns of the strength of ethical culture were identified: moderate, high, increasing, decreasing, and low. The results show that managers exhibiting either the low or decreasing pattern of ethical culture experienced significant changes in their well-being over time. Decreasing or permanently low ethical culture was related to increased cynical attitudes towards work, and to decreased work engagement. On the positive side, stably high ethical culture was associated with enduringly high levels of well-being over time. In sum, low or decreasing ethical culture poses a risk to occupational well-being, whereas an organization with a culture that is perceived as permanently strong represents a favourable work environment.